Extrarenal teratoid wilms tumor - Ashitha K Unny; Balagopal Subramanian; Arathi Srinivasan; Seyed Rabia (Wolters Kluwer Medknow Publications, 2022)
Teratoid Wilms tumor (TWT) is a variant of Wilms tumor. 30 cases have been reported so far. The extrarenal TWT variant has only been 5 in number. We are reporting a case of retroperitoneal TWT in a 6-year-old female child with diagnostic and therapeutic challenges.